Effect of the bileaflet inlet valve angle on the flow of a pediatric ventricular assist device: Experimental analysis. Issue 9 (15th May 2022) - Lemos, Bernardo Luiz Harry Diniz; Bortolin, Vítor Augusto Andreghetto; Amaral, Rodrigo de Lima; Mazzetto, Marcelo; Cestari, Idágene Aparecida; Meneghini, Julio Romano
Abstract: Background: Mechanical heart valves (MHV) and its fluid dynamics inside a pulsatile pediatric ventricular assist device (PVAD) can be associated with blood degradation. In this article, flow structures are analyzed and compared by an experimental investigation on the effect of bileaflet MHV positioned at varying angles in the inlet port orifice of a PVAD. Methods: Time‐resolved particle image velocimetry was applied to characterize the internal flow of the device. St Jude Medical bileaftlet valves were used on the inlet orifice and positioned at 0°, 15°, 30°, 45°, 60°, and 90° in relation to the centerline of the device. Three planes with bidimensional velocity magnitude fields were considered in the analysis with visualization of diastolic jets, device wall washing patterns and flow circulation during emptying or systole of the pump. Also, the washing vortex area, and vertical velocity probabilities of regurgitant flows in the inlet valve were evaluated. Results: The results show that a variation in the angle of the MHV at the inlet port produced distinct velocities, fluid structures, and regurgitant flow probabilities within the device. MHV positioned at an angle of 0° generated the strongest inlet jet, larger vortex area during filling, more prominent outgoing flow, and less regurgitation compared to the angles studied. The presence of unfavorable fluid structures, such as small vortices, and/or sudden flow structure interruption, and/or regurgitation, were identified at 45° and 90° angles. Conclusions: The 0° inlet angle had better outcomes than other angles due to its consistency in the multiple parameters analyzed. Abstract : The 0° inlet angle of a bileaflet mechanical heart valve in a pulsatile pediatric ventricular assist device had better fluid dynamics outcomes when evaluated using time‐resolved particle image velocimetry.